Shostakovich : a life - Fay, Laurel E. (Oxford University Press, 2000)
For this post-cold-war biography of Shostakovich's illustrious but turbulent career under Soviet rule, Laurel E. Fay has gone back to primary documents: Shostakovich's many letters, concert programmes and reviews, newspaper articles, and diaries of his contemporaries.
Includes list of works and glossary of names.
Keywords: Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975.; Chostakovitch, Dmitri Dmitrievitch, -- 1906-1975.; Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975; Šostakovič, Dmitrij D.; Composers -- Soviet Union -- Biography.; Composers -- Russia -- Biography.; Compositeurs -- Russie -- Biographies.; Compositeurs -- URSS -- Biographies.; MUSIC -- Individual Composer & Musician.; BIOGRAPHY & AUTOBIOGRAPHY -- Composers & Musicians.; Composers; Russia; Soviet Union; 4.935.; collective biographies.; Biographies; Biographies.